Commensal mouth bacteria are the main cause of dentoalveolar abscesses in the maxillofacial region - Rusinovci, Sinan; Sejdini, Milaim; Salihu, Sami; Haliti, Naim; Jukić, Doroteja P; Starc, Andrej; Stubljar, David; Jukic, Tomislav (The Journal of Infection in Developing Countries, 2025)
Introduction: The aim of this study was to investigate the bacterial strains that most commonly cause abscesses after failed endodontic treatment. Methodology: 102 pus samples from dentoalveolar abscesses were examined for bacterial growth. Additionally, 102 samples of healthy gingiva from the same patients were swabbed for comparison of etiology. The swabs were inoculated on blood, chocolate, and Schaedler agar plates; and incubated aerobically and anaerobically. Isolated pathogenic bacteria were compared to healthy oral flora from 50 healthy individuals. Bacterial strains were identified using the matrix assisted laser desorption ionization-time of flight (MALDI-TOF) method and susceptibility was tested using VITEK 2. Results: The same microorganism was identified from the healthy and abscess side of the oral cavity in 50.0% of the cases. The most commonly identified healthy aerobic flora were coagulase-negative staphylococci, alpha-hemolytic Streptococcus, Enterococcus, and Klebsiella spp. The most identified anaerobes were Actinomyces, Lactobacillus, and Bacteroides spp. Identification of 6 vancomycin-resistant Enterococcus, 3 amoxiclav resistant Actinomyces spp., 1 extended-spectrum beta-lactamases (ESBL) E. coli, and 2 ESBL Klebsiella spp. were confirmed. A significant correlation was found between prescription of amoxiclav before surgery and isolation of amoxiclav-resistant Actinomyces spp. (p = 0.035). Conclusions: Common oral flora caused dental abscesses. Not much antimicrobial resistance was detected among the bacterial isolates. However, the dentists used antibiotics irresponsibly because a few cases were identified where the bacteria were resistant to antibiotics used prior to removal of dentoalveolar abscesses.